2014
DOI: 10.1111/jcpp.12215
|View full text |Cite
|
Sign up to set email alerts
|

Research Review: The role of diet in the treatment of attention‐deficit/hyperactivity disorder – an appraisal of the evidence on efficacy and recommendations on the design of future studies

Abstract: Nevertheless, there is evidence from well-conducted studies for a small effect of SFFA. Restricted elimination diets may be beneficial, but large-scale studies are needed on unselected children, using blind assessment and including assessment of long-term outcome. Artificial food colour elimination is a potentially valuable treatment but its effect size remains uncertain, as does the type of child for whom it is likely to be efficacious. There are additional dietary supplements that have been used with childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
70
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 97 publications
4
70
1
1
Order By: Relevance
“…Evaluation of reviews and meta-analyses of 11 randomized controlled trials found evidence of a small effect of free fatty acid supplements in ADHD, and an uncertain benefit of artificial color elimination [3]. Similar conclusions are expressed by parents of patients in our neurology clinic for ADHD in children and adolescents at Ann & Robert H. Lurie Children's Hospital of Chicago.…”
supporting
confidence: 60%
“…Evaluation of reviews and meta-analyses of 11 randomized controlled trials found evidence of a small effect of free fatty acid supplements in ADHD, and an uncertain benefit of artificial color elimination [3]. Similar conclusions are expressed by parents of patients in our neurology clinic for ADHD in children and adolescents at Ann & Robert H. Lurie Children's Hospital of Chicago.…”
supporting
confidence: 60%
“…In several studies dietary interventions comprising elimination and restrictive diets have shown promise as effective treatments for ADHD (Nigg and Holton 2014;Stevenson et al 2014). Although it requires significant effort and is difficult to maintain long-term, positive effects have been found following the implementation of very restrictive diets, such as the "few foods" diet (Pelsser et al 2009).…”
Section: The Potential For Antioxidant-related Therapies In Adhdmentioning
confidence: 99%
“…1,2 However, research on the relationship between ADHD and nutrients and food components thus far has yielded inconsistent results. 3,4 Therefore, a dietary approach to ADHD treatment is still regarded as controversial without a comprehensive evidence base.…”
mentioning
confidence: 99%